Penalty stroke in field hockey: A biomechanical study - Hussain, I.; Mohammad, A.; Khan, A.; Bari, M. A.; Ahmad, A.; Ahmad, S. (International Journal of Sports Science and Engineering, 2011)
In the execution and conversion of penalty stroke various factors are involved. Amongst all, biomechanical factor is one of the decisive factor which has been neglected by the Indian researchers. Thus the present study was designed to reveal the associated biomechanical factors of penalty stroke execution. For the purpose of this study six intervarsity level male hockey players were recruited using stratified random sampling method. Their mean age, height and weight were 20 yrs (SD 0.89), 169.67 cm (SD 5.68) and 59.5 kg (SD 4.63), respectively. Three stances i.e. 90 degree, 45 degree and Wrong Foot stances were considered. Each player performed 3 penalty strokes for all pre-assigned stances targeted at four critical corners of the goal post. The 2×2 feet marked scale targets were placed at each critical corner of the goal post to determine the ball accuracy position. To acquire biomechanical quantities, one high speed Canon Legria HF S10 camcorder operating at 60 Hz mounted at a height of 5 feet was placed at 8 meters away, perpendicular to the penalty spot. The players and ball movement during the penalty stroke execution were recorded. Video footages were downloaded, slashed to desired footages and edited for biomechanical analysis. The ball velocity, acceleration, accuracy, stride length, contact time and length, were digitized with the help of Silicon Coach Pro7 motion analysis software. The acquired data of the variables were subjected to descriptive statistical analysis. The results showed that at right top corner in 90 degree stance position subjects gained maximum accuracy that is 52.08 percent with acceleration 14.88 ms-2, velocity 27.30 ms-1, stride length 0.83 mts., contact time 0.055 sec. and contact length 0.915 mts. At right ground corner in wrong foot stance position subjects gained accuracy 50 percent with acceleration 20.85 ms-2, velocity 27.84 ms-1, stride length 1.12 mts., contact time 0.045 sec. and contact length 0.93 mts. At left top corner in 45 degree stance position subjects gained accuracy 47.91 percent with acceleration 17.34 ms-2, velocity 30.35 ms-1, stride length 1.256 mts., contact time.061 sec. and contact length 1.08 mts. At left ground corner in 45 degree stance position subjects gained accuracy 47.92 percent with acceleration 19.92 ms-2, velocity 33.60 ms-1, stride length 1.278 mts., contact time 0.06 sec. and contact length 1.131 mts.